Rare Run-Over Clinical Case. Evisceration of the Intestines through the Wrist - Strelčenko, Jekaterina; Vasiljevaitė, Diana; Chmieliauskas, Sigitas; Laima, Sigitas; Stasiūnienė, Jurgita; Petreikis, Paulius (Acta medica Lituanica, 2025)
Background: Deaths resulting from car-pedestrian collisions are frequently encountered in forensic practice. Such accidents often cause extensive, multi-system injuries, many of which are concealed beneath minimally damaged soft tissues and may not be immediately visible externally. Common external injuries include extensive skin abrasions, subcutaneous hematomas, and lacerations. Internally, these incidents typically result in multiple bone fractures and severe organ ruptures. A less frequent but noteworthy injury is the evisceration of abdominal organs through ruptures in the diaphragm, rectum, or abdominal wall. This report presents a unique case of small intestine evisceration through damaged skin on the wrist.Materials and methods: The literature search was conducted in the PubMed and Google Scholar databases using keywords. The analysis focused on scientific literature that was published in last 10 years but also referred to older scientific papers with strong arguments. To the best of our knowledge, there are no reported cases of evisceration of abdominal contents through the damaged skin of the lower arm (wrist). A clinical case examination from the Lithuanian State Forensic Medicine Service data was performed.Case presentation: A 70-year-old woman was injured in the run-over accident by a truck. The victim died at the scene. External examination revealed multiple injuries, including significant soft tissue deformities in the left arm. During the internal examination of the corpse, multiple fractures with ruptures of internal organs were found. Only isolated fragments of intestinal loops were present in the abdominal cavity. Evisceration of the small intestines through the left upper arm and forearm was found.Conclusions: Run-over accidents involving heavy vehicles are a common cause of fatal injuries. These incidents often result in extensive lacerations, multiple comminated fractures, and severe damage to internal organs. In rare cases, evisceration of internal organs can occur through various anatomical sites. This case demonstrates that evisceration can occur not only through common locations such as the diaphragm, abdominal wall, rectum, or vagina but also through atypical sites, such as the skin of the wrist. In such cases, it is particularly important for a forensic pathologist to assess the damage of clothing and to evaluate the macromorphological appearance of the injuries to determine the mechanism of injury.
Keywords: run-over; visceral evisceration; multiple traumas; blunt trauma; autopsy; forensic pathology